PERBEDAAN TINGKAT KEPUASAAN PASIEN UMUM DAN PASIEN DENGAN BADAN PENYELENGGARA JAMINAN SOSIAL - Harris Rambey; Beni Satria; Marice Simarmata; Anggi Isnani Parinduri; Ester Ariani Tarigan (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
Quality health care was often associated with satisfactory health care. The patient's satisfaction with the health service was the level of one's feelings after comparing the results received with expectations. Patient satisfaction on health service can be seen tangible, responsiveness, reliability, assurance, and attention (empathy). This study aims to determine differences in patient satisfaction level of social insurance provider body with general patients at Grandmed Hospital Lubuk Pakam 2017. This type of research was quantitative research is comparative. The population in this research are all inpatients of Grandmed Hospital Lubuk Pakam as much as 324 people, purposive sampling technique, data collection method by interviewing indirectly by used questionnaires, data analysis using T-Independent test. Based on the result of the research, it was known that there was difference of patient satisfaction level of social insurance provider body with general patient based on physical evidence (tangible) with p value = 0,002, reliability with p = 0,005, responsiveness with p = 0,007, Based on assurance with p = 0,002, based on empathy (empathy) with p = 0,006. It was advisable for the nursing staff of the grandmed hospital to be able to perform the service very well so that the patient was satisfied with the existing services and raises the patient's interest to return if they are sick.